Citizenship Education in Defending Nationalism in the Digital 4.0 Era to Face the Society 5.0 Era - Theodore Wibisono Rumpak; Muhammad Fahmi Faturrahman; Kevin Ramadhan; Yusuf Akmal Agam (Green Publisher Indonesia, 2022)
Background : The Digital Era 4.0 is a new phase in the industrial era that focuses on automation, interconnectivity, machine learning, real time data and automation. Purpose : Various countries have prepared and are willing to complete in the digital 4.0 era, so not many countries face various problems. Method : on the learning citizenship, this relates to the era of society 5.0 where the two don’t have much difference. Result : The world community is required to possess the ability to solve complex problems , think critically and ambiguity. So with the presence of era society 5.0 , it can be a solution.The principle is based on the role of humans who live side by side with technology. Conclusion : So that humans balance real time data between economic progress with solving various social problems using a system that connects the real world with the virtual world.